Theoretical and Experimental Study of the Distribution of Stress Waves in Linear Viscoelastic Media - N. V. Olali; M. A. Orukari; N. M. Zazymko; M. P. Malezhyk (Archives of Current Research International, 2019)
The influence of viscoelastic properties of an optically sensitive epoxy material on the propagation of pressure waves in a rod was carried out. In the article of determination of the visco-elastic operator, the theoretical relations for the case of propagation of longitudinal waves are obtained based on the results of a photoelastic experiment. The noticeable difference between the experimental data and the calculation at the pulse end can be explained by the change in the propagation velocity of the Fourier decomposition component of the real impulse.